2011
DOI: 10.1038/jhg.2011.127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the CYP17A1 and NT5C2 genes are associated with a reduction in visceral and subcutaneous fat areas in Japanese women

Abstract: Visceral fat accumulation has an important role in increasing the morbidity and mortality rates, by increasing the risk of developing several metabolic disorders, such as type 2 diabetes, dyslipidemia and hypertension. New genetic loci that are associated with increased systolic and diastolic blood pressures have been identified by genome-wide association studies in Caucasian populations. This study investigates whether single nucleotide polymorphisms (SNPs) that confer susceptibility to high blood pressure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
0
36
1
1
Order By: Relevance
“…A recent report also indicated that rs4846567 was strongly associated with the V/S ratio in women (p = 0.0004), but not men (p = 0.05) 14) . We have recently reported that rs1004467 in the cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1) gene and rs11191548 in the 5'-nucleotidase, cytosolic Ⅱ (NT5C2) gene were significantly associated with reductions in both VFA and SFA in women, but not in men 21) . Our studies and previous reports highlight the need for a better understanding of the underlying molecular mechanisms in the sex differences in the regulation of the distribution of body fat.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report also indicated that rs4846567 was strongly associated with the V/S ratio in women (p = 0.0004), but not men (p = 0.05) 14) . We have recently reported that rs1004467 in the cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1) gene and rs11191548 in the 5'-nucleotidase, cytosolic Ⅱ (NT5C2) gene were significantly associated with reductions in both VFA and SFA in women, but not in men 21) . Our studies and previous reports highlight the need for a better understanding of the underlying molecular mechanisms in the sex differences in the regulation of the distribution of body fat.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 These patients agreed to undergo CT testing (in the supine position) to determine the VFA and SFA values at the umbilical level (L4-L5). Both VFA and SFA values were calculated using the FatScan software program (N2system, Osaka, Japan).…”
Section: Study Subjectsmentioning
confidence: 99%
“…12 We have previously reported that among the single-nucleotide polymorphisms (SNPs) susceptible to obesity, [13][14][15] rs7498665 in the SH2B adaptor protein 1 (SH2B1) gene was associated with VFA, 16 and that among hypertension-susceptible SNPs, 17,18 rs1004467 in the cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1) gene and rs11191548 in the 5¢-nucleotidase, cytosolic II (NT5C2) gene were significantly associated with both reduced VFA and SFA in women, indicating a genetic background to central obesity. 19 Visceral fat obesity is also a risk factor for the development of type 2 diabetes. Several studies have investigated the association of type 2 diabetes loci from GWAS with body fat and BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral fat is evaluated by waist circumference, waist-hip ratio, bioelectrical impedance, or more precisely, measurement of visceral fat area (VFA) using computed tomography (CT) [1,15]. Numerous studies have shown that VFA is influenced by genetic loci [16][17][18][19][20][21]. However, despite the observation that ADIPOQ is a promising candidate gene for visceral fat accumulation [22,23], few studies have reported a link between ADIPOQ polymorphisms and VFA.…”
Section: Participantsmentioning
confidence: 99%
“…ADIPOQ polymorphisms are associated with insulin resistance in Japanese women Aya Kitamoto 1) , Takuya Kitamoto 1) , Rina So 2) , Tomoaki Matsuo 2) , Yoshio Nakata 2) , Hideyuki Hyogo 3) , Hidenori Ochi 3) , Takahiro Nakamura 4) , Seika Kamohara 5) , Nobuyuki Miyatake 6) , Kazuaki Kotani 7) , Ikuo Mineo 8) , Jun Wada 9) , Yuji Ogawa 10) , Masato Yoneda 10) , Atsushi Nakajima 10) , Tohru Funahashi 11) , Shigeru Miyazaki 12) , Katsuto Tokunaga 13) , Hiroaki Masuzaki 14) , Takato Ueno 15) , Kazuaki Chayama 3) , Kazuyuki Hamaguchi 16) , Kentaro Yamada 17) , Toshiaki Hanafusa 18) , Shinichi Oikawa 19) , Toshiie Sakata 20) , Kiyoji Tanaka 2) , Yuji Matsuzawa 7) and Kikuko Hotta 1)…”
unclassified